Фонд времени и мероприятия в социальной сфере - Бардакова С. Н.; Журавлева И. В.; Караханова Т. М. Татьяна Муртазаевна; Лакомова Н. В.; Маслов Е. В. Евгений Владимирович; Патрушев В. Д. Василий Дмитриевич; Петрухина Л. А.; Подовалова Р. Я. (Москва, Наука, 1989)
Исключено из фонда НТБ ТПУ